2007
DOI: 10.1111/j.1365-2036.2007.03335.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosa of coeliac disease patients produces antiendomysial and antitransglutaminase antibodies: the diagnostic usefulness of an in vitro culture system

Abstract: SUMMARYBackground Antiendomysial (EmA) and antitransglutaminase (anti-tTG) antibodies are the most specific indirect marker of coeliac disease (CD). It is not known whether the oral mucosa of patients with CD is able to produce these antibodies or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Recent studies have also shown a close association between oral and intestinal mucosa in patients with celiac disease, a complex autoimmune enteropathy induced by dietary gluten [7][8][9]. Consequently, the Ni-patch-induced oral mucosa lesions are probably related to bowel damage that occurs after ingestion of Ni-containing foods that in turn, causes the A Ni patch may also cause development of general reactions such as itching and dermographia, suggesting that the omPT can effectively identify Ni-sensitive patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent studies have also shown a close association between oral and intestinal mucosa in patients with celiac disease, a complex autoimmune enteropathy induced by dietary gluten [7][8][9]. Consequently, the Ni-patch-induced oral mucosa lesions are probably related to bowel damage that occurs after ingestion of Ni-containing foods that in turn, causes the A Ni patch may also cause development of general reactions such as itching and dermographia, suggesting that the omPT can effectively identify Ni-sensitive patients.…”
Section: Discussionmentioning
confidence: 95%
“…The aim of the present study was to investigate the relationship between intestinal symptoms and Ni intake by a novel oral mucosa patch test (omPT), based on recent studies that have shown a close association between oral and intestinal mucosal compartments in patients with celiac disease, a complex autoimmune enteropathy induced by dietary gluten [7][8][9]. The omPT is described for the first time in the present study.…”
mentioning
confidence: 96%
“…A subcutaneous oral mucosal challenge with gliadins, on the other hand, significantly increased the number of CD4 + and CD8 + T cells in the oral lamina propria of CD patients, but not in nonceliac controls, suggesting an induced oral mucosal immune response to gluten in CD . Cultured oral mucosal and duodenal biopsies from CD patients showed a comparable anti‐TG2 and anti‐endomysal antibody response in the culture media, with a sensitivity between 57 and 100% , likely depending on biopsy size . Saliva as a diagnostic fluid for CD has also been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia without other clinical signs of intestinal malabsorption is one of the most common extra-intestinal manifestations of CD [37]. CD is frequently diagnosed in patients referred for evaluation for iron deficiency anaemia, which is found in 1.8-14.6% of patients [38].…”
Section: Ferropenic Anaemia and Associated CDmentioning
confidence: 99%